Flora of Bahia: Portulacaceae - Coelho, Alexa Araújo de Oliveira P.; Giulietti, Ana Maria (SITIENTIBUS série Ciências Biológicas, 2006)
A floristic survey of the Portulacaceae species in Bahia, Brazil is presented as a contribution to the study of the flora in the state. The work was based on the morphological analysis of specimens from herbaria and from materials collected as part of the Flora of Bahia Project. Nine species are recognized in Bahia, including two species of Talinum – T. paniculatum (Jacq.) Gaertn. and T. triangulare (Jacq.) Willd., and seven species of Portulaca – P. elatior Mart., P. halimoides L., P. hirsutissima Camb., P. mucronata Link., P. oleracea L., P. umbraticola Kunth, and P. werdermannii Poelln. Analytical keys for the genera and species are presented together with descriptions, illustrations, and general notes on the species.